Penerapan Peningkatan Pengetahuan dan Perilaku Kebiasaan Cuci Tangan Melalui Metode Bermain Efektif di TK Al-Iman, Padi, Desa Bontomacinna, Kecamatan Gantarang, Kabupaten Bulukumba - Susiani Susiani; Tri Surya Ayu Lestari; Hera Hera; Ismatul Auliyah; Nur Azila Putri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The age of 4-6 years is an age that is vulnerable to disease because it is at this age that children's motoric starts to be active. Without realizing it, what children do is often close to germs that can cause diseases such as flu, cough, diarrhea. Hand washing is the process of mechanically removing dirt and dust from the skin surface and reducing the number of microorganisms. The purpose of hand washing is to eliminate the number of microorganisms. This activity is carried out through the means of joint learning activities in the form of face-to-face in groups, given counseling, including: material and practice of wet hand washing with running water and soap and dry hand washing with a hand sanitaizer. The results of this activity were analyzed using a fun learning method. The data used is numerical data from the observation of hand washing skills checklist. From the test results there is an effect of providing counseling on hand washing techniques on the hand washing skills of kindergarten students. The habit of washing hands using soap from an early age, it is hoped that later they will become a generation that is aware of the importance of cleanliness, not only personal hygiene, but also environmental hygiene. Not only that, with this simple thing that is done regularly and purposefully, children will later learn to do other habits correctly. One way to prevent children from getting sick is by washing hands. This handwashing habit should be instilled since.